2011
DOI: 10.3382/ps.2010-01283
|View full text |Cite
|
Sign up to set email alerts
|

Content and uptake of minerals in the yolk of broiler embryos during incubation and effect of nutrient enrichment

Abstract: Although embryo and chicken growth and development rely on mineral nutrition, information on mineral levels in the egg compartments during incubation is limited. Accordingly, we examined P, Ca, Fe, Zn, Cu, and Mn levels in the yolk of breeder eggs during incubation and the effect of embryonic mineral (with specific nutrients) enrichment on yolk mineral levels and consumption. First, fertile eggs were examined on day of setting (DOS), embryonic day (E) 11, E13, E15, E17, E19, E20, and day of hatch (DOH) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 24 publications
8
85
1
Order By: Relevance
“…Shell Mg content was unaffected by ambient temperature but it was significantly higher in eggs from older hens as reported by Waddell et al (1991), who suggested that magnesium distribution would also alter with increasing bird age, by Cusack et al (2003), who revealed a greater increase in magnesium content in the outer region of egg shells from older birds, and by Yair and Uni (2011), who assumed that layer age-related changes occur in shell mineral composition. This higher Mg content in older hens is the more interesting because there were no differences in egg shell thickness between young and old birds.…”
Section: Discussionsupporting
confidence: 62%
“…Shell Mg content was unaffected by ambient temperature but it was significantly higher in eggs from older hens as reported by Waddell et al (1991), who suggested that magnesium distribution would also alter with increasing bird age, by Cusack et al (2003), who revealed a greater increase in magnesium content in the outer region of egg shells from older birds, and by Yair and Uni (2011), who assumed that layer age-related changes occur in shell mineral composition. This higher Mg content in older hens is the more interesting because there were no differences in egg shell thickness between young and old birds.…”
Section: Discussionsupporting
confidence: 62%
“…The yolk is the major storage compartment of nutrients for embryos but most of the trace elements (Zn, I, or Se) are exhausted by the late embryonic stage. In ovo supplementation of iron, zinc, copper and manganese helped to improve the mineral levels in the yolk along with higher embryonic mineral consumption . The decreased hatchability in the selenium‐treated eggs could be attributed to dose‐related toxicity that usually occurs when the body's ability to excrete excess Se is compromised .…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of trace elements such as zinc (Zn) and iron (Fe) decreases significantly to almost 50% in the first 2 weeks of embryonic life and are mostly consumed from the residual yolk by the day of hatch (DOH) . Zinc (Zn) and selenium (Se) play a vital role in numerous biological processes as a component of many enzymes and are also essential for growth, skeletal development and immune competence in chicken .…”
Section: Introductionmentioning
confidence: 99%
“…For this method to be effective, it is important to select the optimal embryonic stage for the delivery. In chickens, in ovo technology has been used mainly on the 18 th day of embryonic development (ED) for the intramuscular injection of the vaccines against Marek's disease [14] or on the 17.5 th day of ED for in ovo feeding of the embryos with the nutrients (e.g., carbohydrates, beta-hydroxy-beta-methyl-butyrate, minerals, vitamins and oligosaccharides) that enhance development of the chicks and growing birds [1519]. But, for the in ovo delivery of prebiotics and synbiotics, an earlier time point, i.e., the 12 th day of ED, has been proven empirically, more effective [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most basic phenotype that reflects the primary reaction of an individual to the particular treatment is the modulation of gene expressions in specific cells or tissues. In our earlier studies, we determined that in ovo delivery of synbiotics, consisting of raffinose family oligosaccharides (RFO) and Lactococcus lactis subsp., significantly up-regulated IL-4 , IL-6 , IFNB , and IL-18 in the spleen (S) and down-regulated IL-4 , IL-6 , IL-8 , IL-12 , IFNB , and IFNG in the cecal tonsils (CT) of a native chicken breed at 42 days old [19]. We also detected a down-regulation of immune-related gene expression in the S and CT of broiler chickens injected in ovo with inulin or galactooligosaccharides (GOS) combined with L .…”
Section: Introductionmentioning
confidence: 99%